Exploring Curriculum-Based Learning for English Language Learners - Ayu Putriana Lestari; Sabarun Sabarun; Zaitun Qamariah (CV. Ulil Albab Corp, 2023)
Examining curriculum-based learning for English language learners (ELLs) is the goal of this journal article. Effective instructional strategies that address the particular needs of ELLs are becoming more and more important as a result of the increasing diversity in classrooms. The theoretical underpinnings of curriculum-based learning are examined in this article along with its potential advantages for ELLs. The difficulties of applying this strategy in various educational settings are also covered, along with some practical considerations. The goal of curriculum-based learning for English language learners (ELLs) is to create and use teaching tools and methods that are specifically suited to the linguistic and academic requirements of ELL students. This method acknowledges the particular difficulties ELLs face in learning the language while also engaging with content knowledge in a range of subject areas. This journal article explores the theoretical underpinnings, essential elements, and potential advantages of curriculum-based learning for English language learners (ELLs). The focus of this journal article's thorough overview of curriculum-based learning for ELLs is on its importance in promoting inclusive education for a variety of student populations. Teachers and policymakers can support the academic success and linguistic development of ELL students by making decisions based on their understanding of the theoretical underpinnings, essential elements, and potential advantages of this approach.